Clueless in academe : how schooling obscures the life of the mind - Graff, Gerald (Yale University Press, 2003)
Gerald Graff argues that our schools and colleges make the intellectual life seem more opaque, narrowly specialised, and beyond normal learning capacities than it is or needs to be. Left clueless in the academic world, many students view the life of the mind as a secret society for which only an elite few qualify. In a departure from standard diatribes against academia, Graff shows how academic unintelligibility is unwittingly reinforced not only by academic jargon and obscure writing, but by the disconnection of the curriculum and the failure to exploit the many connections between academia and popular culture. Finally, Graff offers a wealth of practical suggestions for making the culture of ideas and arguments more accessible to students, showing how students can enter the public debates that permeate their lives.